Políticas curriculares e atlas escolares municipais: contribuições para o estudo do lugar - Honda, Janiane Divina dos Santos (2017)
The concept of place is one of the essential concepts for teaching Geography in the early years of elementary school, because it allows the student to give meanings to the space in which he lives, to understand the relationships that it has with society in the construction of citizenship. The construction of the concept of place in teaching Geography come true for the content taught, that are suggested in the documents of the curricular policies applicable in the country and to serve as a reference for teachers to organize their work. Among such policies, are the law of guidelines and Bases (LDB), the National curriculum guidelines (DCN) and the National curricular parameters (PCN), that address the study of place in the initial years of elementary school. Also in this context, local curriculum policies. School mapping, also present in the curricular policies, provides opportunities for the study of place for being a language that works as representations of the geographical space in the school. Therefore, we must have means and resources to help the teacher and the student in this process. The municipal school through atlas of cartographic language, contributing to the construction of the concept of place in teaching Geography in a systematic and meaningful and thus constitute as materials relevant to the study of place, by articulating the relationship of the identity of the society with the space which is inserted and to which she belongs. The distributed textbooks to schools cannot cover the particularities of this same space. Therefore, this work has the objective of analyze the didactic-pedagogical proposal of Atlas Municipal School by establishing a dialogue with the curricular policies pertaining to the study of place in School Geography for elementary school. This investigation we chose a qualitative approach as most appropriate methodological option to the objective proposed. Through the research participant, undertake a theoretical analysis on the construction of the concept of place, policies governing educational curriculum on teaching Geography in Brazil in the state of Goiás and the monitoring of the use of the Municipal School Atlas Goianira (GO). In this sense, the subjects of the research were students and teachers from the first stage of the elementary school of the municipal schools of Goianira (GO). For data collection, the research had as methodological procedure the study and bibliographical analysis of public policies governing the education system in Quezon City and with direct observation, interviews with teachers and directors of school units governed by the Board of education of Goianira (GO). The final considerations point reflections about the potential trainer "of atlas municipal school for teachers and students, as didactic material that covers requirements for the study of place in teaching Geography in the early years of elementary school.